KURIKULUM PENDIDIKAN TINGGI ISLAM DI ERA KOMPETISI - Hasbi Indra (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2017)
Islamic higher of Education are born in colonialism era at 1940, set by community of Islamic teacher at West Sumatera. The first after colonialism of Dutch and Japan and proclamation of Indonesia by Soekarno-Hatta its are established by Hatta and Natsir the Islamic higher of education at Jakarta in wich named ADIA, and also the following years in Yogyakarta established PTAIN. And 1960 ADIA and PTAIN are both merger and be named IAIN as centres of institution in Jakarta and Yogyakarta. The Instituions until now still exist and in globalization era and are face crusial challenges ahead. Its era are development of science and technology (IPTEK), such as in fields of medicine and others and to has great benefits for humanity, for their needs. But, also there are the side negative its makes people becoming trapped in the "doomsday", like ozone problem, water contaminated by industrial Its was marked by characterized that competation among the resoucres of humans of nations. Thats condition are face for Islamic higher of education as need a respon. With the effect those problems alumni of Islamic higher of education must to readiness with deep-knowledge, profesional and have skill and have soul entrepreneurship. For that Islamic higher of education need review visions and curriculum are face for that the fenomenon. Curriculum a part of pillar urgent for made generation in the furure from the higher of Islamic education. The curriculum are based of esensial of humans have thinks, bodies and spiritual all wholly potentials of humans with brains, emotion and pshicomotor, so the teacher take learned with that approach its.